(untitled) (Bangladesh Pharmaceutical Journal, 2016)
The present investigation was designed to prepare controlled release microspheres of carbamazepine using two polymers of different solubility and permeability characteristics, Ethocel standard 45 premium and Eudragit RL 100. The drug release profile was optimized with the aid of design of experiments (DoE). Microspheres of combined polymers were designed according to 22 factorial central composite design (CCD), taking drug loading and polymeric ratio as the independent variables. Total thirteen batches were prepared. The dependent variables were percentage of drug released in 3 hours and 6 hours and mean dissolution time (MDT). The regression parameters of the developed model and graphical interpretation for each response with statistical significance were calculated by using Minitab 17. The relationship between the experimental variables and responses were evaluated by generating response surface plots. Increased amount of Eudragit RL 100 had impact on surface morphology of prepared microspheres. It produced larger holes on the surface due to its higher permeability characteristics. Polynomial mathematical models generated for various response variables using multiple linear regression analysis, were found to be statistically significant (p < 0.05). One optimum formulation (O1) was selected based on USP specification and the second optimum formulation (O2) was selected for the maximization of MDT (hours). Batch O1 showed 22.85 % and 48.78 % drug release after 3 and 6 hours, respectively which were found to be in close agreement with those predicted by the mathematical model. Another optimum formulation, batch O2 showed MDT as 160.61 hours. Bangladesh Pharmaceutical Journal 19(2): 152-160, 2016